Application Of Neuro – Fuzzy Systems In Gene Classification - Deepika Malhotra, Shivangi Chawla, Meghana Aggarwal (International Journal of Scientific Research and Management (IJSRM), 2015)
Neuro-Fuzzy Systems are one of the important research topics in computer science nowadays. They combine the approaches of Neural networks with the logics and calculations of Fuzzy. This paper demonstrates the applications of neuro – fuzzy systems in the classification of genes. Here the concepts of Fuzzy Matching will be applied in order to calculate the probabilities of occurrence of these gene traits in the future generations by studying the patterns of Gene Transfer in the previous generations. ‘Classification of genes’ will help in finding those genes which can be dominant in the future generations and can be the cause of some chronic hereditary diseases. These diseases if possible can be avoided by predicting the probability of its occurrence in the next generation and taking the required precautions and medical treatments.